Cytologic Features of Lymphoepithelioma-Like Carcinoma Involving the Parotid: A Case Report. (11th September 2019) - Chen, Fei; Modi, Lopa; Zamuco, Ronaldo; Yee-Chang, Melissa
Abstract: Fine-needle aspiration biopsies (FNABs) are a common modality used in the evaluation of salivary gland neoplasms. We present the cytologic and histologic features of a rare case of lymphoepithelioma-like carcinoma (LELC) in a 40-year-old Hispanic male with a 1.0-cm painless well-circumscribed parotid mass that had been present for 8 years. FNAB smears showed cohesive groups of intermediate-sized basaloid cells with vesicular nuclei, occasional pleomorphic nuclei and prominent nucleoli, and spindled morphology. Mature lymphocytes were seen in the background, either adjacent to the atypical epithelial cells or dispersed in the background. This lymphoid background raises considerations of salivary gland neoplasms that can have prominent lymphocytic backgrounds, such as acinic cell carcinoma and, more commonly, Warthin's tumor or metastasis involving intraparotid lymph node. Surgical resection of the parotid showed syncytial sheets of predominantly undifferentiated cells with spindled to epithelioid morphology and occasional prominent nucleoli and focal areas of squamous differentiation. The background showed dense areas of lymphocytes with germinal center formation. Immunohistochemical (IHC) stains showed positive reactivity for p63, p40, and EBV in situ hybridization (EBV ISH) in the tumor cells and negative reactivity for p16. The findings were supportive of LELC if a metastasis from the nasopharynx was excluded. A subsequent nasopharyngeal biopsy was benign. Although histologic features of LELC are well established, we identified rare case reports describing the cytomorphology in the literature. Cytopathologists should be aware of this lesion as another salivary gland neoplasm that can show lymphocytes admixed with the tumor cells and a distinct lymphoid background. The basaloid appearance and cytologic atypia should distinguish it from acinic cell carcinoma and Warthin's tumor. However, metastatic lesions should also be considered with a distinct lymphoid background and need to be clinically excluded before establishing the diagnosis of LELC.